Influence of health education on knowledge, attitude, and practices toward organ donation among dental students - Samata Srinivasula; Adepu Srilatha; Dolar Doshi; Bandari Srikanth Reddy; Suhas Kulkarni (Wolters Kluwer Medknow Publications, 2018)
OBJECTIVES: Knowledge, attitudes, and behaviors are essential factors in fostering an environment that positively influences organ donation rates. Thus, the present study aimed to assess the impact of intervention (classroom education) on knowledge, attitude, and practices on organ donation. MATERIALS AND METHODS: A questionnaire-based interventional study was conducted among 112 dental house surgeon students, Hyderabad. A 27-item self-administered questionnaire was distributed to students as a pretest and collected back after completion. Then, a session on organ donation was delivered in a lecture hall setting instilling the basic facts about organ donation. Posttests using the same questionnaire were filled after the intervention and 2 weeks later. RESULTS: Responses on knowledge obtained from the subjects showed significant changes in several key areas from baseline to postintervention and at follow-up. More than 50% of study subjects had a positive attitude regarding organ donation. There was a significant increase in the number of subjects who pledged/signed to donate an organ (before - 14.3%, postintervention - 50%, and at follow-up - 60.7%; P < 0.05). Pairwise comparison revealed a significant increase in the mean knowledge, attitude, and practice scores at postintervention and at follow-up of 2 weeks in comparison to the baseline scores. Female subjects and subjects following Hindu religion had good knowledge, positive attitude, and good practice. CONCLUSION: The one brief educational intervention had significantly increased perceived knowledge of organ donation and positively influenced attitude and practices to organ donation among dental students.